Control Refinement Using Particle Methods - Saba Zia; Atif Qayyum; Fahad Mumtaz Malik; Mohammad Bilal Malik (IEEE Access, 2022)
The paper presents a control scheme for the real-time tracking problem of nonlinear systems subjected to hard nonlinearities. The proposed tracking controller introduces a refining component in the control input designed for the nominal plant model. The refining component compensates for tracking performance degradation caused by modelling uncertainties and external disturbances. The refining component is modelled as a random signal, the probability density function is expressed as a combination of finite weights typical of particle methods. The weights are updated based on sequential tracking error data. The proposed algorithm is simulated for an inverted pendulum affected by Coulomb friction. Comparison with existing techniques exhibits remarkably superior tracking performance.